Unraveling the role of galectin-3 in cardiac pathology and physiology - Seropian, Ignacio M.; Cassaglia, Pablo; Miksztowicz, Verónica; González, Germán E. (Frontiers in Physiology, 2023)
Galectin-3 (Gal-3) is a carbohydrate-binding protein with multiple functions. Gal-3 regulates cell growth, proliferation, and apoptosis by orchestrating cell-cell and cell-matrix interactions. It is implicated in the development and progression of cardiovascular disease, and its expression is increased in patients with heart failure. In atherosclerosis, Gal-3 promotes monocyte recruitment to the arterial wall boosting inflammation and atheroma. In acute myocardial infarction (AMI), the expression of Gal-3 increases in infarcted and remote zones from the beginning of AMI, and plays a critical role in macrophage infiltration, differentiation to M1 phenotype, inflammation and interstitial fibrosis through collagen synthesis. Genetic deficiency of Gal-3 delays wound healing, impairs cardiac remodeling and function after AMI. On the contrary, Gal-3 deficiency shows opposite results with improved remodeling and function in other cardiomyopathies and in hypertension. Pharmacologic inhibition with non-selective inhibitors is also protective in cardiac disease. Finally, we recently showed that Gal-3 participates in normal aging. However, genetic absence of Gal-3 in aged mice exacerbates pathological hypertrophy and increases fibrosis, as opposed to reduced fibrosis shown in cardiac disease. Despite some gaps in understanding its precise mechanisms of action, Gal-3 represents a potential therapeutic target for the treatment of cardiovascular diseases and the management of cardiac aging. In this review, we summarize the current knowledge regarding the role of Gal-3 in the 2 This is a provisional file, not the final typeset article pathophysiology of heart failure, atherosclerosis, hypertension, myocarditis, and ischemic heart disease. Furthermore, we describe the physiological role of Gal-3 in cardiac aging.